Psychologiczne uwarunkowania preferencji w zakresie kształtu systemu politycznego w Polsce na podstawie badań empirycznych - Turska-Kawa, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
The paper looks at the issue of the psychological conditioning of the preferences concerning the shape of governance system and the system of political parties in Poland in the light of empirical research (N=1086), carried out in 2009. The analysis takes into account the variables of self-assessment, dispositional optimism, self-efficacy and dispositional fear. These variables, accounting for the cognitive functioning of individuals, the level of their involvement and motivation, have turned out to be significant when differentiating individuals’ preferences concerning political systems.